Essays in Environmental and Energy Economics - Farhidi, Faraz (2018)
This dissertation consists of three separate chapters using theory, simulation, empirical techniques, and also an experiment to address several questions relating to utilizing fossil fuel-based energy and its consequences on environment and society. My first essay, titled “Endogenous Population Growth in a Macro Environmental Model,” simulated, based on U.S. calibrated data, the effect of utilizing clean energy vs. fossil fuel energy on long-run economic growth and its impact on the total welfare of the society. I present a dynamic growth model that explicitly allows for the interaction between an economy and an environment. I allow for endogenous population growth, where population is affected by living standards and level of industrialization as well as natural resources, indirectly through production. Endogenizing the population growth the growth rate of GDP per capita is lower under endogenous population scenario relative to exogenous population growth. Imposing carbon-tax element on the energy producers’ profit would accelerate the adaptation of the clean energy and sustain fossil fuel resources for a more extended period and would increase the individuals’ long-term total consumption. The second essay, titled “Having Skin in the Energy Game: The Impact of Social Norms on Energy Regime Changes.” In this paper, I present a survey study in an experimental field context that explores the social norms effect on petition signing, focusing on clean energy adaptation instead of fossil fuel energy. I use multiple energy consumption data at the national level for selected countries. This research highlights that not only social norms could be compelling individuals’ behavior, but also that they are sensitive to the types of information which are disclosed to them. I develop my final essay, titled “Energy Fallout: Air Pollution Effects on Environmental and Social Externalities,” estimated the effect of different types of energy consumption on mortality rates and violent crimes. This study aims to estimate a reduced-form model that could explain and then verify the possible relation between crime rates and mortality rates that arise from the different energy regimes utilization in affected regions, using mechanism effect analysis; while air pollution and level of income are two channels of this causation analysis